Geography fieldtrips in New Zealand at secondary school and undergraduate level in the second half of the 20th century and beyond : a thesis presented in partial fulfilment of the requirements for the degree of PhD in Geography at Massey University, Palmerston North, New Zealand - Stirling, Susan (Massey University, 2006)
This research involves an exploration of the practice of geography fieldtrips in New Zealand. Fieldtrips are often part of geography courses at university and secondary school, but little research has been undertaken as to why they are so frequently a part of geography courses, how they relate to geographers' theoretical understandings, and what geographers hope to achieve by running fieldtrips. A humanist approach was chosen for the study. A number of university lecturers and secondary school geography teachers were interviewed, who have organised, executed, and evaluated fieldtrips. Drawing on Buttimer's (1983a) work, the concepts of milieu, metaphor, and meaning have been used as key foci for the research. Using structured interviews, the background and memories, or milieu, of the geographer was established to understand influences on his or her academic development. Textbooks read and published, courses attended and given, and the school curriculum were discussed in relation to how they affected fieldtrips. A second theme constructed the nature of the fieldtrip as metaphor or narratives, and showed how the geographer demonstrated his or her geographical knowledge and values. The third theme determined meaning by eliciting the values and convictions important to the geographer in the fieldtrip. The meaning of fieldtrips related to geographers' own approach to the subject, their episteme or philosophy of geography, which transcends their teaching and research interests. This affected the manner in which the geographers run fieldtrips, the metaphor that they practised, from a focus on mapping, to foci on gathering statistics, understanding society, and concentrating on matters of difference in society. Four main approaches were identified: classifying the world, applying general theories to explain the world, using structures to interpret the world, and deconstructing the world. This study contributes to understanding the role of geography fieldtrips in New Zealand. Insights are provided into geographical learning and teaching by reflecting on the extensive history of fieldtrips in geography, clarifying how geographers' theoretical underpinnings relate to fieldtrips, and explaining how the essence of fieldtrips relates back to lecturers' and teachers' philosophies of geography.
Keywords: Geography study; Secondary school geography; Undergraduate geography; Geography field trips; Geography teaching